The Influence of Cooperative Learning Through Authentic Assessment-Based Jigsaw on Social Development of Early Childhood - Karta, I Wayan; Rachmayani, Ika; Rasmini, Ni Wayan (Jurnal Pendidikan Indonesia, 2021)
The early childhood education system nowadays requires the use of authentic assessment in schools. Authentic assessment is an integrative method of assessing the learning process, reflective to the real-world situations, using varieties methods and holistic criteria to assess the cognitive, affective, and skills in early childhood. Social development occurs dominantly after physical, cognitive, and language developments. Based on the minimal developmental standard, many early-childhood children show substandard development in environment adaptation ability, self-managing ability, responsibility, ability to follow rules, sharing, respecting others, cooperation, toleration, and emotional expression. This study aims to identify the influence of cooperative learning through authentic assessment-based jigsaw in the social development of early childhood. This study uses a pre-test post-test design on 50 subjects aged 5-6 years old. The experiment was carried out in 4 stage with 4 learning sub-themes. Data collected with a 1-4 scale observation instrument to get quantitative data and analyzed using t-Test. Results from data analysis concluded that cooperative learning through authentic assessment-based jigsaw has a positive influence on social development in early childhood. We recommend the implementation of this method to optimize social development in early childhood.